Teachers’ Strategies for Implementing Integrated Learning in First Grade at Public Elementary Schools - Melisa Ade Irma Umu Khalsum; Silviana Rahma Dewi; Ninda Beny Asfuri (ICEETE Conference Series, 2026)
This study aims to describe teachers’ strategies for implementing integrated learning in first grade at SD N 2 Tlogotirto. The study employed a descriptive qualitative approach using interview and observation data as the primary source. The data were collected through teacher interviews, classroom observation, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that integrated learning is understood by the teacher as “pendekatan yg menggabungkan berbagai mata pelajaran ke dalam satu tema sentral.” The teacher’s strategies include mapping basic competencies or indicators, selecting relevant themes, preparing lesson plans or teaching modules, applying student-centered learning, using play-based learning, employing flexible instructional media, and conducting authentic assessment. The teacher also used visual, audio, concrete, technology-based media, and student worksheets to support students’ understanding. The main challenges included students’ limited attention span, difficulty in connecting several subjects into one theme, limited time, curriculum load, and the complexity of planning. The study concludes that integrated learning in first grade can be implemented effectively when the teacher creates active, interactive, meaningful, and enjoyable learning activities